Effect of low temperature on the nitrogen nutrition of annual medics: Preliminary results - Obaton M.; Materon L.; Zaklouta M.; Gintzburger G. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
The 'Medics' (annual Medicago) developed for the Australian ley-farming system under fairly mild winter temperature are not adapted to most of the agroecological zones encountered in North Africa and West Asia. To allow sheep to graze during winter in places where there is temperature below 10 deg., the ability of various medics to germinate, fix nitrogen and produce herbage around 10 deg. was studied. 16 accessions of M. aculeata, M. rigidula, M. tornata, M. truncatula, M. polymorpha, M. rotata were tested for germination. A following study on seven M. aculeata accessions showed that M. aculeata appears to be the most permissive accession for early germination and growth at low temperature but requires an efficient rhizobial strain. An experiment in controlled environment conducted to test 5 strains of Rhizobium melioti on four accessions of M. aculeata confirmed these results and indicated an interaction between rhizobium and accession of M. aculeata for early nodulation. On a field experiment including inoculated, not inoculated and not inoculated with nitrogen fertilizer treatments, N-fertilized plants assimilated soil nitrate and grew during winter, so at the end of the winter the dry weight of N-fertilized plants was two times the weight of the inoculated or control plants. There was no nitrogen fixation during the cold period; this activity began later during spring.At harvest, herbage yields of N-fertilized and plants inoculated were similar and significantly higher than the uninoculated ones. These results suggest that an early planting enables the medic plants to establish a maximum of plant biomass and active nodulation before winter when photosynthesis and nodulation continues. M. aculeata is highly specific for Rhizobium meliloti.Selection of Medicago and Rhizobium for early nodulation and nitrogen fixation is necessary.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)